Prevalence to Toxoplasma gondii and Neospora caninum antibodies in goats from Mossoró, Rio Grande do Norte - Lima, Júlia Teresa Ribeiro de; Ahid, Sílvia Maria Mendes; Barrêto Júnior, Raimundo Alves; Pena, Hilda Fátima de Jesus; Dias, Ricardo Augusto; Gennari, Solange Maria (Brazilian Journal of Veterinary Research and Animal Science, 2008)
Toxoplasmosis is a disease affecting all endothermic animals, including humans. Infection can cause reproductive failures that generate severe economic losses in goats. Neospora caninum is a protozoan recently recognized, also causing reproductive abnormalities in goats, but there are few studies. Serum samples from 381 goats (324 females and 57 males) bred in 14 farms from Mossoró County, Rio Grande do Norte State, northeastern region of Brazil, were tested to determine the prevalence of T. gondii and N. caninum using the indirect fluorescent antibody test. Sera that reacted to dilutions >; 1:64 and >; 1:50, respectively, were considered positive. In 13 farms (92.8%), there were seropositive goats to T. gondii and in four farms (28.6%), there were seropositive animals to N. caninum. T. gondii prevalence was 17.1% (65/381) and N. caninum prevalence was 1.05% (4/381). There was no association between seropositivity to T. gondii or N. caninum and gender, presence of reproductive failures or presence of cats or dogs in the farms. Results indicate low N. caninum prevalence among goats from Mossoró County and T. gondii is widely distributed among goat herds in the same region.